1998
DOI: 10.1074/jbc.273.14.8003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Activity between α and β Type I Interferons Explored by Mutational Analysis

Abstract: Type I interferon (IFN) subtypes ␣ and ␤ share a common multicomponent, cell surface receptor and elicit a similar range of biological responses, including antiviral, antiproliferative, and immunomodulatory activities. However, ␣ and ␤ IFNs exhibit key differences in several biological properties. For example, IFN-␤, but not IFN-␣, induces the association of tyrosine-phosphorylated receptor components ifnar1 and ifnar2, and has activity in cells lacking the IFN receptor-associated, Janus kinase tyk2. To define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 52 publications
(82 reference statements)
4
48
0
Order By: Relevance
“…These results are in agreement with published data describing the presence of speci®c functional receptors for IFN-a in a series of pediatric tumors, including Ewing's sarcoma, and in cell lines derived from these tumors (Rosolen et al, 1997). Despite the fact that all type I IFNs bind to the same receptor and activate a common set of signaling elements, there is now accumulating evidence of dierences in their signaling pathways (Croze et al, 1996;Domanski et al, 1998;Runkel et al, 1998). For instance, selective Jak-1 phosphorylation induced by IFN-b in human myocardial ®broblasts was recently reported (Grumbach et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with published data describing the presence of speci®c functional receptors for IFN-a in a series of pediatric tumors, including Ewing's sarcoma, and in cell lines derived from these tumors (Rosolen et al, 1997). Despite the fact that all type I IFNs bind to the same receptor and activate a common set of signaling elements, there is now accumulating evidence of dierences in their signaling pathways (Croze et al, 1996;Domanski et al, 1998;Runkel et al, 1998). For instance, selective Jak-1 phosphorylation induced by IFN-b in human myocardial ®broblasts was recently reported (Grumbach et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a and IFN-b (type I IFNs) share a common receptor (Uze et al, 1990;Novick et al, 1994;Domanski et al, 1996); IFN-g (type II IFN) binds to a dierent cell surface receptor (Aguet et al, 1988). Recent reports showed that the subunits of its receptor engage IFN-b in a set of interactions distinct from those of IFN-a (Croze et al, 1996;Domanski et al, 1998;Runkel et al, 1998). Early events in type I IFN signaling are tyrosine phosphorylation of the type I IFN receptor subunits (IFNAR1 and IFNAR2), and the activation of the receptor-associated Tyk-2 and Jak-1 Janus kinases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mutagenesis studies of the IFNaR2-2 chain showed differential receptor activation since (i) intracellular deletions abrogated only the IFN␤ and not the IFN␣-induced antiviral response, while activation of the JAK/Stat pathway was equal in both cases (28), and (ii) extracellular mutations created receptor complexes that showed preferential binding for each of the ligands (27). It is also possible to obtain mutations in IFN␤ that mimic IFN␣ activity (29). These data suggest that other mechanisms may be responsible for generation of signal diversity apart from utilization of cytokine-specific receptor components.…”
mentioning
confidence: 99%
“…The main question at issue is whether their activity is redundant or they are characterized by unique functions (6). Studies of the biological effects of natural IFN subtypes have shown that their activities can vary greatly (7)(8)(9)(10). IFN-␣8, for example, is the most potent antiviral protein (11), while IFN-␤ has a higher potency in inhibiting the growth of certain tumors and is used in the treatment of multiple sclerosis (12)(13)(14).…”
mentioning
confidence: 99%